Survival of Salmonella in Diced Onions Washed by Different Concentrations of Pineapple Vinegar During Refrigerated Storage (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Salmonella contamination has been repeatedly linked to diced onions. This study investigated the efficacy of washing solutions using pineapple vinegar at varying concentrations (0%, 5%, and 15%) on the survival of S. Typhimurium in diced onions during refrigerated storage conditions. Briefly, diced onions (50 g) were inoculated with S. Typhimurium at ~ 8 log CFU/g and then submerged in the washing solutions for 2 min. Inoculated onions were allowed to dry for approximately 1 hr, divided into 1 g portions and stored at refrigerated conditions for 12 days. Salmonella was enumerated on Xylose Lysine Deoxycholate (XLD) media at predetermined sampling points during storage. Overall, S. Typhimurium exhibited a little reduction (5.63 ± 0.34 log CFU/g) at 0% washing solution, whereas 6.25 ± 0.53 log CFU/g at 15% pineapple vinegar during the entire storage. Salmonella populations showed moderate reductions at 5% pineapple vinegar washing solution at the beginning of storage, but remained stable throughout the storage period. These findings suggest that pineapple vinegar could serve as a natural alternative to chemical preservatives, providing greater microbiological safety for diced onions while preserving their quality. The study highlights the role of natural antimicrobial agents in enhancing food safety and prolonging the shelf life of fresh produce.
Keywords: Diced onions; Salmonella Typhimurium; Natural preservative; Pineapple vinegar; Antimicrobial properties